Kurdish religiosity: development and validation of a Religiosity Scale in a Muslim Kurdish context. Issue 9 (26th November 2018) - Ismail, Azad Ali
ABSTRACT: Religiosity takes various forms even within the same religion. This study aimed to develop and validate a Kurdish scale for assessing religiosity. A total sample of 469 Muslim students took part in the study. A convenient sample of 249 university students responded to the initial form of the scale. The scale had good test–retest reliability and internal consistency. Exploratory factor analysis yielded four factors, namely relationship with Allah, commitment to religious teachings, belonging, and forgiveness and love. Another sample of 220 university students answered three sets of questionnaires; Kurdish Religiosity Scale as well as Oxford Happiness Inventory and Perceived Stress Scale. Religiosity was positively correlated with happiness and negatively with perceived stress.